'You shall not wash my feet eis ton aiōna' (John 13.8) Time and Ethics in Peter's Interactions with Jesus in the Johannine Narrative - Rahmsdorf, Olivia 1988- (2019)
In search of 'timeless' norms or behavioral examples, the Gospel of John seems to offer few options. The principle of brotherly love exemplified in the act of foot washing is often considered as the only example of ethically significant material in the Johannine narrative. However, by taking a closer look at the 'tempo' of actions and the characters' orientation in time, we can understand that Peter's protest against the foot washing is not only in favor of norms that secure existing hierarchies, but is driven by temporal norms, i.e. his genuine fear of death. Peter's protest (Jn 13.8) indicates his desire for the eternal life promised by Jesus (Jn 11.25-26) and at the same time it serves as a defense against the foot washing as pointing to his own burial, which he infers from Jesus' earlier interpretation of the anointing of his feet (Jn 12.7). Starting from this vantage point, a multitude of other interesting (time) conflicts and behavioral patterns come to light, revealing both Jesus, through his act of foot washing, and all of those who encounter him in their own actions and reactions, as instructive moral agents.
Keywords: Johannine ethics; John 13.1-20; Peter; laying down one's life; time and ethics